2016
DOI: 10.1089/nat.2015.0592
|View full text |Cite
|
Sign up to set email alerts
|

Delivery, Effect on Cell Viability, and Plasticity of Modified Aptamer Constructs

Abstract: AS1411 is a g-quadruplex-forming aptamer capable of selectively entering cancer cells by nucleolin receptor-mediated uptake. In this study, we investigated the cell internalization properties and plasticity of AS1411 carrying different locked nucleic acid-containing cargo oligonucleotides (ONs) for delivery into A549 and U2OS cells. We found that internalization efficiency is highly governed by ON cargo chemistry and composition since the inherent antitumor properties of AS1411 were lost when attached to a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 287 publications
(303 reference statements)
0
3
0
Order By: Relevance
“…Further, NCL-blocked cells displayed much lower ROS production after treatment with TMPyP DNM Apt-gc34@SPION NPs with respect to blocked cells. Results of MTT assay demonstrated that cell viability was highly reduced in NCL-non-blocked cells indicating that AS1411 structure plays an important role for the cellular internalization of the designed drug delivery system resulting in a higher cell inhibition 82,121 . A significant reduction in cell growth under the visible light was observed and was due to the synergistic effect of DNM and TMPyP.…”
Section: Other Types Of As1411 Aptamer-conjugated Npsmentioning
confidence: 99%
“…Further, NCL-blocked cells displayed much lower ROS production after treatment with TMPyP DNM Apt-gc34@SPION NPs with respect to blocked cells. Results of MTT assay demonstrated that cell viability was highly reduced in NCL-non-blocked cells indicating that AS1411 structure plays an important role for the cellular internalization of the designed drug delivery system resulting in a higher cell inhibition 82,121 . A significant reduction in cell growth under the visible light was observed and was due to the synergistic effect of DNM and TMPyP.…”
Section: Other Types Of As1411 Aptamer-conjugated Npsmentioning
confidence: 99%
“…Its internalization efficiency highly depends on the chemistry of the oligonucleotides. LNA substitutions were investigated with this GQ [ 165 ]. The formation of a GQ from a G-rich 25-mer section of the vascular endothelial growth factor aptamer was highly facilitated by LNA modifications.…”
Section: Stabilization or Destabilization Of A Gq By The Same Syntmentioning
confidence: 99%
“…Conventional optimization methods include the following: (1) Substituting a natural nucleotide for a nucleotide modified with a group to avoid degradation of the nucleic acid[44]; (2) Chemically synthesizing a mirror image sequence of the selected aptamers with high plasma and serum stability to enhance the stability of aptamers to make them have significant therapeutic potential[45]; (3) Modifying aptamers with locked nucleic acids to enhance their ribozyme resistance. Methylene-linked 2'-oxygen and 4'-carbon in carbohydrate residues have strong ability to hybridize with nucleic acid molecules and are not easily degraded by enzymes[46]; and (4) Covalently attaching PEG or cholesterol to aptamers, prolonging their residence time in the human body and reducing renal filtration rate[47,48]. The half-life of survival of aptamers in human physiological environment can be extended from a few minutes to several hours by one or more of the above methods, and aptamers with modifiable properties are superior to antibodies or polypeptides in the diagnosis and treatment of tumor diseases.…”
Section: Selex Methods For Screening Aptamersmentioning
confidence: 99%